Workshop Pembuatan Preparat Semi Permanen sebagai Media Pembelajaran bagi Guru Biologi di MA NW Kayangan Kabupaten Lombok Barat - Efendi, Ismail; Sukri, Akhmad; Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
Efforts to improve the quality of science learning require various breakthroughs, both in curriculum development, learning innovation, learning media and fulfillment of educational facilities and infrastructure. To improve student achievement, teachers are required to make learning more innovative which encourages students to learn optimally both in independent learning and in classroom learning. In order for learning to be more optimal, it is also necessary that learning media must be effective and selective in accordance with the subjects taught in improving student achievement. Learning media is one of the important components in learning. Media is a tool to understand the concept or subject matter. Biology is a part of science (science) which contains scientific concepts and develops science process skills. Science process skills can be possessed by students through direct observation of objects that involve various student activities in the classroom and outside the classroom. Lately, the implementation of the science learning process, especially Biology with the approach of science process skills and the use of learning media is still not optimal. There are still few teachers who want to develop science process skills in learning biology. Likewise, there are still teachers who are less creative in using learning media for various reasons, such as the availability of tools and practicum materials, limited funds, time and others. To find alternative solutions to the problems above, a workshop on making semi-permanent preparations was held for teachers. With the aim of training teachers to make preparations that are very important in supporting the implementation of biology practicum in schools. The results of this community service activity show that the teachers are very enthusiastic and feel the benefits of this activity in the learning process. This activity is expected to be improved again while still paying attention to the needs of teachers with other materials so that they can open the insight of Biology teachers in innovating to create various learning media needed.